KONTRIBUSI PERAN ORANG TUA TERHADAP KREATIVITAS ANAK DI SMP NEGERI 4 SAMPIT - Sudarmono Sudarmono; Apuanor Apuanor; Dianira Dianira (Jurnal Paedagogie Media Kependidikan, Keilmuan dan Keagamaan, 2018)
Parents have a very influential role in providing education as a personal development effort of children. Parents can have a creative child if they apply appropriate methods of educating children. In the right way, the creativity of the child will definitely grow well and optimally. This study was conducted to determine the influence of the role of parents to the creativity of children. The Population of this research are 244 students of VIII grade in SMP Negeri 4 Sampit and then only 25% or 63 students will be objects. Analysis techniques of this research is simple linear regrecy analysis.Based on the results of this study that is the contribution of parents to the development of children's creativity in SMP Negeri 4 Sampit 2016/2017 academic year. Contribution of parent's role to creativity is 0,260 or 26%. It means that the parent role variable influences 26% to the creativity of the child.